TCMQMS System: A digital twin and blockchain-based platform for tracing the whole process of Chinese medicine quality information - Han, Peiheng; DUN, Linan; Tian, Ye; Li, Zhichun; LI, Wenxu; YANG, Hetong; WANG, Bohan (Food Science and Technology, 2023)
Traditional Chinese medicine is an important medicine and health food in China. In the process of making Chinese medicines, the main active ingredients of the medicines are highly dependent on the production environment due to the special physical characteristics of the medicines themselves. Any slight change in the environment can lead to changes in the active ingredients as well as the final efficacy, even affecting the patient treatment cycle, and this characteristic is not conducive to quality control by national drug quality regulators. In order to enhance the quality management of TCM, a blockchain and digital twin based whole process monitoring system for TCM quality is proposed: Traditional Chinese Medicine Quality Monitoring System (TCMQMS), in order to achieve a whole process, full scope and highly transparent TCM quality monitoring model for TCM production from the source of cultivation to the final patient. And. A blockchain platform based on Fabric blockchain data development platform as well as Sia distributed data storage was designed. With the help of Sia distributed storage technology, the amount of data storage is significantly compressed, which achieves the purpose of unifying the huge information data flow into the TCMQMS system and quickly building the system platform using the Fabric platform. In addition, in order to ensure that data is read and written in real time during the manufacturing and transportation of Chinese medicine, environmental sensors, such as temperature and humidity sensors, are placed in the Chinese medicine processing plant and in the transport sector. The environmental sensors, such as temperature and humidity sensors, are placed inside the Chinese medicine processing plants and transport vehicles. The environmental data is combined with the production data recorded by the TCMQMS system and sent to the digital twin TCM manufacturing simulation environment in real time, and through the simulation of the TCM manufacturing environment, the TCM quality environment parameters are continuously iteratively updated to be more suitable for production. This is coupled with real-time linkage with environmental sensors to achieve real-time adjustment of environmental parameters. In addition, the TCMQMS system records the entire process data, giving each data block a unique and tamper-proof hash value and CA certificate, so that when there is a possible quality problem, the hash value and CA certificate will be used to quickly trace the person responsible and the details of the environment in which the TCM was produced in real time. Finally, we present a real-life example of the use of the TCMQMS system to validate our proposed approach.